Grammar instruction for grammatical competence / Swee Ai Teoh - Teoh, Swee Ai (Universiti Teknologi MARA Shah Alam, 2017)
This paper is based on a study which investigated the effectiveness of explicit grammar instruction. The instruction was set in the context of teaching students to write literature reviews. A pre-test and a post-test were carried out to ascertain whether there was improvement in the students' command of verb tenses after a lesson where the students were given instruction on the different tenses that are used in literature reviews. The findings of this study lead to the conclusion that explicit grammar instruction is most effective for students who are least grammatically competent.